Brain structure correlates of foreign language learning experiences - Wang, Xiaoqiao; Kim, Jae-Yoon; Kim, Jun-Ho; Choi, Yoonseok; Ha, Eun-Gyu; Kim, Dong-Hyun; Sul, Sunhae; Yang, Sujin; Song, Hyun-joo (Frontiers in Human Neuroscience, 2025)
Previous research demonstrates that bilingual experiences produce dynamic and variable structural adaptations in the brain. However, most studies focus on individuals who naturally acquire multiple languages, leaving the neural effects of long-term foreign language learners with limited exposure less understood. In this study, we examined 32 young adult long-term foreign language learners in South Korea to determine how age of acquisition, proficiency, and daily use shape gray matter volume and white matter integrity in predominantly monolingual environments. We found structural changes in brain regions involved in language control and executive function. Voxel-based morphometry analysis revealed that earlier foreign language acquisition was significantly associated with greater gray matter volume in the left inferior parietal lobule (uncorrected p < 0.001) and the left thalamus (uncorrected p < 0.001). Higher daily use was significantly associated with greater volume in the right inferior parietal lobule (uncorrected p = 0.001) but reduced it in the right anterior cingulate cortex (uncorrected p < 0.001). Tract-based spatial statistics analysis further showed that earlier age of acquisition was significantly associated with better white matter integrity in the splenium of the corpus callosum (FWE-corrected p = 0.009), while higher daily use was significantly associated with better integrity in the body of the corpus callosum (FWE-corrected p = 0.030). These findings suggest that even limited but sustained exposure to a foreign language can lead to significant structural adaptations, broadening our understanding of language-related neuroplasticity beyond traditional bilingual contexts.